The relation between Hebrew and Turkic in Crimean Karaim literature on the basis of a translation of the Hebrew drama Melukhat Sha’ul - Smętek, Dorota (Karaite Archives, 2013)
This paper discusses three topics related to a Crimean Karaim translation of the Hebrew drama entitled Melukhat Sha’ul. The translation was made in the first half of the nineteenth century, approximately in the 1840s, by a Karaim scholar named Abraham ben Yashar Lutski. The first part of this article is devoted to the characteristics of relations between the Karaims and the Rabbanites at the turn of the eighteenth and nineteenth centuries in the context of their literary activity. It is followed by a short description of the plot of the drama and its connections and deviations from the biblical events presented in The First Book of Samuel. The third part of the article analyzes the influence of Hebrew on the language of the Crimean Karaim translation of Melukhat Sha’ul. Moreover, attention is drawn to the manner in which Hebrew vocabulary related to magic was translated into Turkic. For the purpose of this paper magical terms, which are present in the Hebrew drama, are compared with their counterparts in the Turkic translation.